Importance of potassium ions for ribosome structure and function revealed by long-wavelength X-ray diffraction - Rozov, Alexey; Khusainov, Iskander; El Omari, Kamel; Duman, Ramona; Mykhaylyk, Vitaliy; Yusupov, Marat; Westhof, Eric; Wagner, Armin; Yusupova, Gulnara (Nature communications, 2019)
The ribosome, the largest RNA-containing macromolecular machinery in cells, requires metal ions not only to maintain its three-dimensional fold but also to perform protein synthesis. Despite the vast biochemical data regarding the importance of metal ions for efficient protein synthesis and the increasing number of ribosome structures solved by X-ray crystallography or cryo-electron microscopy, the assignment of metal ions within the ribosome remains elusive due to methodological limitations. Here we present extensive experimental data on the potassium composition and environment in two structures of functional ribosome complexes obtained by measurement of the potassium anomalous signal at the K-edge, derived from long-wavelength X-ray diffraction data. We elucidate the role of potassium ions in protein synthesis at the three-dimensional level, most notably, in the environment of the ribosome functional decoding and peptidyl transferase centers. Our data expand the fundamental knowledge of the mechanism of ribosome function and structural integrity. Metal ions play essential roles in myriads of biological processes, from catalytic co-factors to supporting protein and nucleic acid structures. Here the authors use long-wavelength X-ray diffraction to locate hundreds of potassium ions taking part in the formation of rRNA tertiary structure, mediating rRNA–protein interactions and supporting ribosomal protein structures and function.